The Illustrated Afterlife of Terence's Comedies (800-1200) - Keefe, Beatrice Radden, author.
1 online resource.
Keywords: Widely read as school texts, the comedies by the Roman dramatist Terence have come down to us in hundreds of medieval copies. Fourteen of the manuscripts produced between 800 and 1200 were given some kind of illustration. In this volume, Beatrice Radden Keefe explores the semiotics of the imagery found in the earliest illustrated Terence manuscripts, and its relationship to the iconography of comedy and theatre from antiquity. She examines six further manuscripts to show how later illustrators abandoned this imagery to varying degrees, finding new emphases and creating new layers of meaning. Illustrators of Terence, it is demonstrated here, brought a range of interests to illustrating the comedies, clarifying their narrative, incorporating social commentary and moralisation, and linking them with Christian allegorical traditions.